Meaning of the family in ancient rome - Смілянець, Ірина Петрівна; Смилянец, Ирина Петровна; Smilyanets, Iryna P. (My University, 2016)
In Ancient Rome institute of the Roman family is one of the specific. The specificity of it lies in the fact that not every family and not all related nature of men and women recognized marriage, and generate legal consequences. The main role was at legal relationships, as for blood connection between persons – it was secondary.

У стародавньому Римі інститут римської сім’ї відноситься до числа специфічних. Специфікація полягає в тому, що не кожна сім’я і не всякі спорідненого характеру відносини чоловіка і жінки визнавалися шлюбом, що породжує правові наслідки. Головну роль відігравало агнатичне споріднення, іншими словами – юридичне, а кровний (когнатичний) зв’язок вважався другорядним.

В древнем Риме институт римской семьи относится к числу специфических. Специфика эта заключается в том, что не каждая семья и не всякие родственного характера отношения мужчины и женщины признавались браком, порождающим правовые последствия. Главную роль играло агнатическое родство, другими словами – юридическое, а кровная (когнатическая) связь считалась второстепенной.
Smilyanets I. P. Meaning of the family in ancient rome / I. P. Smilyanets // Часопис цивілістики. – 2016. – Вип. 20. – С. 176-179.
Keywords: family relationship; kinship; nepotism; marriage; Roman law; сімейні правовідносини; спорідненість; свояцтво; шлюб; римське право; семейные правоотношения; родство; своячество; брак; римское право